Microbiological safety of milk and processing and consumption behaviour in pastoral areas in southern Ethiopia - Amenu, K.; Szonyi, Barbara; Wieland, Barbara; Grace, Delia (Hawassa University, 2016)
The objective of the present study was to assess the behaviour of people in milk production and consumption using qualitative methods. Further, the study involved the microbiological quality and safety assessment of milk and traditional dairy products along milk value chains. The investigation involved largely women given that women are customarily involved in milk handling and processing. Individual semi-structured interviews, focus group discussions, and observations were used to (1) document milk production and processing practices, (2) assess perception on quality and safety of milk including perceived criteria for good milk, (3) assess awareness on milkborne diseases, and (4) evaluate milk boiling practices. The interviews and discussions were documented using field note and audio recording which later were transcribed and analysed by identifying the themes. For the microbiological assessment, a total of 203 samples: 145 pooled milk, 40 directly from udder and 18 ititu (fermented whole milk curd with whey removed) were analysed for E. coli count and selected pathogens (E. coli O157:H7, Listeria spp. and Staphylococcus aureus). The result showed that cow milk is processed into different products such as ititu, butter milk, butter and ghee. Goat milk is either directly consumed by children during herding or added to tea instead of further processing. Camel milk production is practiced only in some villages and appreciated for its larger volume especially during dry season and widely consumed and marketed fresh. Most of the respondents stated that humans cannot get disease from milk consumption and boiling of fresh milk is not a common practice in the area because people believe that “vitamin is destroyed when boiled” and “boiled milk is considered as dead”. On the other hand, milk is usually consumed with tea by adding the milk into hot boiled and filtered tea. Women mentioned smoking as a way to ensure quality, shelf life and safety of milk and traditionally produced dairy products. However, observation of milk handling and processing practice revealed apparent unhygienic conditions. E. coli was detected in 51.7% of the analysed samples with a mean count of 5x105 CFU/ml. The study also revealed that 2.5%, 10.8% and 1.5% of the samples harbour E. coli O157:H7, Staphylococcus aureus and Listeria spp., respectively. Thus the findings of this study highlight the need to promote hygienic practises and measuring the effect of these. In addition there is a need to closely engage with local communities to improve their understanding on milk safety risks and thus to facilitate a change in practices.